EXPERIENCE ECONOMY AND DIGITAL MARKETING STRATEGIES IN ENHANCING HOTEL COMPETITIVENESS - Sri Marini; Superwiratni; Ilham Fajri; Ita Karnita (EKUITAS (Jurnal Ekonomi dan Keuangan), 2025)
Consumers are increasingly seeking memorable experiences, not only standard hotel services, but also driving intense competition in West Java's hospitality industry. Although several strategies have been implemented, a literature gap remains in relation to the role of customer engagement as a mediating variable between strategy and hotel competitiveness. Therefore, this study aims to analyze the effect of experience economy and digital marketing strategies on hotel competitiveness, both directly and through customer engagement. The research covers 320 three- to five-star hotels in West Java, with an estimated annual guest population of 57,600. A total of 400 respondents were selected using Slovin's formula, which incorporates a 5% margin of error and employs a multistage sampling approach. Data was analyzed using the SEM-PLS method. The results indicate that both strategies significantly enhance hotel competitiveness, both directly and indirectly, through the partial mediating role of customer engagement. These findings underscore the importance of combining experiential and digital approaches to foster a deeper emotional connection with customers and gain a competitive edge. This study contributes to the theoretical development of hospitality management. It also provides practical insights for hotel managers in West Java to enhance their competitiveness by implementing experience-driven and digitally oriented strategies tailored to meet customer expectations.